(untitled) (DIWANGKARA: Jurnal Pendidikan Bahasa, Sastra dan Budaya Jawa, 2024)
This research in the backgound by the limited knowledge of the public regarding the function of oral literature contained in folklore. This study analyzes the folklore "Dumadine Makam Ki Ageng Kurahan" originating from Suruhan Hamlet, Rogomulyo Village, Kaliwungu District, Semarang Regency. The problem studied is the function of the folklore "Dumadine Makam Ki Ageng Kurahan". The purpose of this study is to describe the functions contained in the folklore "Dumadine Makam Ki Ageng Kurahan". This study uses a qualitative descriptive approach based on the functional theory of David Kaplan and Manners. Methods of data collection with interview techniques and field observations. The results of the analysis show that the folklore "Dumadine Makam Ki Ageng Kurahan" has 4 functions as follows; (1) social function, (2) religious/spiritual function, (3) cultural function, and (4) natural preservation function.